Environmental and social impacts of wind energy: a view point with reference to India - Gawande, Abhishek; Chaudhry, Pradeep (Ecological Questions, 2019)
Energy is a basic requirement for economic development and is an integral part of every sector of Indian economy. Renewable energy is increasingly seen as the energy choice of the future as it offers an alternative yet effective solution to reduce carbon emissions and minimize the tradeoffs between environment and energy development. India is increasingly adopting responsible renewable energy technologies and taking positive steps towards carbon emissions, cleaning the air and ensuring a more sustainable future. A large body of literature addressing the issues regarding large negative environmental externalities caused by electricity generation from fossil fuels based energy is available; yet, literature dealing with environmental and social impacts of wind power energy plants, especially in developing countries like India is almost absent. This study is expected to contribute towards filling this gap by synthesizing information about the environmental and social impacts of the wind power projects especially in Indian context.